Economic impacts of a supporting scheme on domestic energy consumption in Bolivia: A quasi-experimental approach - Ricardo Nogales; Andrea Alcaraz; David López Soto; Pauline Ravillard; Sergio Ballon; Michelle Hallack (Inter-American Development Bank (IDB), 2023)
The Bolivian government fostered an electricity cost supporting scheme to attenuate the effect of the nationwide full lockdown on domestic consumption during the COVID-19 pandemic. This paper evaluates its effect on the levels of energy consumption during lockdown, and the monetary savings it implied for beneficiaries. It finds that the absolute gains of the scheme are concentrated among better-off households as measured by income or years of schooling. However, the relative gains of the supporting scheme are clearly concentrated in the worse-off part of the population.
Keywords: H23; H31; H53; I38; Q41; D12; 330; Electricity Subsidy; Household Consumption and Behaviour; RedistributiveEffects